Peripheral Ameloblastoma: A Case Report and Review of Literature - V. T. Beena; Kanaram Choudhary; R. Heera; R. Rajeev; R. Sivakumar; K. Vidhyadharan (Case Reports in Dentistry)
Peripheral ameloblastoma, a rare and unusual variant of odontogenic tumour, comprises about 2–10% of all ameloblastomas. The extraosseous location is the peculiar feature of this type of tumour, which is otherwise similar to the classical ameloblastoma. This paper describes a case of peripheral ameloblastoma in a 67-year-old female affecting the lingual alveolar mucosa of the mandibular 32–34 region which was clinically diagnosed as pyogenic granuloma. This paper becomes important due to availability of all data, makeing it a well-documented case.